IMPLEMENTASI METODE EVEN-RODEH CODE UNTUK KOMPRESI KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) BERBASIS ANDROID - Nopiyah Belia Batubara; Taronisokhi Zebua (STMIK Budi Darma, 2019)
Smartphones in addition to being a smartphone communication tool also functions as a tool for finding information. One application that is currently widely used by students and the public is KUHP application that run in mobile. KUHP application is an application that contains material of criminal laws. The KUHP application has large material and is stored in the application database after it is installed. The large size of the database of the Criminal Code application causes the need for large memory space at mobile. This has become one of the causes of smartphone memory performance to be reduced and slow. Compression technique can be used as a solution to the problem above. Compression aims to compress large data sizes into smaller ones, so that the required storage space decreases. This study describes how to do the compression process of the KUHP application material based on the Even Rodeh Code algorithm. Based on the results of tests conducted to compress 280 bits of data, it was found that the size of the data after being compressed was 176 bits, with compression ratio is 62.8%, ratio of compression is 1.59 bits, and redundancy is 37.2%.Keywords: Compression, KUHP Aplication, Even Rodeh Code, Database